2016
DOI: 10.3390/rs8100810
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison of Total Suspended Sediment Algorithms: A Case Study of the Last Decade for MODIS and Landsat-Based Sensors

Abstract: A quantitative comparative study was performed to assess the relative applicability of Total Suspended Solids (TSS) models published in the last decade for the Moderate Resolution Imaging Spectroradiometer (MODIS) and Landsat-based sensors. The quantitative comparison was performed using a suite of statistical tests and HydroLight simulated data for waters ranging from clear open ocean case-1 to turbid coastal case-2 waters. The quantitative comparison shows that there are clearly some high performing TSS mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 101 publications
0
20
0
Order By: Relevance
“…Additionally, water depth, or bottom reflectance, impacts observed reflectance independently from IOPs. For best performance, empirical algorithms typically need to be parameterized individually for a given optically complex water body [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, water depth, or bottom reflectance, impacts observed reflectance independently from IOPs. For best performance, empirical algorithms typically need to be parameterized individually for a given optically complex water body [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…These algorithms are generally easier to use for conventional applications of remotely sensed TSS estimates, and their physical basis is more straightforward [16]. In a comprehensive quantitative review of published TSS algorithms, Dorji et al 2016 [44] found that optically based algorithms generally perform better than empirical algorithms in waters with unknown composition.…”
Section: Discussionmentioning
confidence: 99%
“…¼ 511:9 Â R rs 645 r 2 ¼ 0:88; NRMSE ¼ 12:18%; n ¼ 21; n represents the total number of points=match À ups used ðNovoa et al:; 2017Þ (1) Multiple studies have successfully used a similar approach to determine either turbidity or SPM in moderately turbid waters (Dorji and Fearns, 2016), therefore it was considered to be appropriate for our study also. Previous authors used also the green spectral band to retrieve SPM in the Bay of Biscay (Gohin et al, 2005;Gohin, 2011), but such approach might underestimate the higher concentrations close to the coast and river mouth.…”
Section: Satellite Data and Productsmentioning
confidence: 99%